Determinants of Improvement in Cardiopulmonary Exercise Testing After Left Ventricular Assist Device Implantation. Issue 5 (September 2018) - Rosenbaum, Andrew N.; Dunlay, Shannon M.; Pereira, Naveen L.; Allison, Thomas G.; Maltais, Simon; Stulak, John M.; Joyce, Lyle D.; Kushwaha, Sudhir S.
Abstract : Although improvement in cardiac output and hemodynamic parameters is routinely demonstrated in patients implanted with continuous-flow left ventricular assist devices (CF-LVADs), improvement in exercise capacity is inconsistently seen. Our purpose was to determine whether native cardiac factors, LVAD factors, or comorbid factors were associated with lack of improvement. Review of all patients undergoing preimplant cardiopulmonary exercise testing (CPET) and CPET on LVAD therapy at one institution was performed between 2007 and 2014 (n = 49). Comprehensive assessment of echocardiographic parameters, right heart catheterization data, medications, and comorbid illness was undertaken. There was no mean improvement in peak oxygen consumption (VO2 ; 11.8–12.4 ml/kg/min; p = 0.26), although exercise time (5.1 [46% predicted] to 5.8 min [56% predicted]; p = 0.02) and nadir of the ratio of minute ventilation to carbon dioxide production slope (VE/VCO2; 39–36; p = 0.001) improved. Factors most strongly associated with improvement in VO2 were Heartmate II pulsatility index (PI; R = 0.48; p = 0.001), power ( R = −0.40; p = 0.009), pump flow ( R = −0.40; p = 0.008), and pump speed ( R = −0.32; p = 0.04). Peak heart rate (HR) was also associated with improvement in VO2 ( R = 0.41; p = 0.004). Left ventricular ejection fraction (LVEF; R = 0.004; p = 0.77), right ventricular (RV) function ( R = 0.22; p = 0.28), and aortic valve opening ( R = 0.20; p = 0.57) were not associated with improvement in VO2 . Our data suggest that less reliance on LVAD support was modestly associated with improvement in exercise capacity. Further studies should seek to determine the optimal level of device support prospectively in relation to exercise capacity.